Training on the Development of Artificial Intelligence-Based Teaching Media Oriented to Deep Learning for Creating Innovative Digital Classrooms in Merdeka Belajar - Firdiawan Ekaputra (Mattawang: Jurnal Pengabdian Masyarakat, 2026)
The purpose of this activity is to improve teachers' abilities in developing artificial intelligence based teaching media to create innovative digital classrooms in the Kurikulum Merdeka. This training activity was held in September 2025 and was attended by 22 teachers from all subject areas at SMA Negeri 8 Muaro Jambi. The methods applied in this training included presentations on innovative teaching media, an introduction to deep learning-oriented artificial intelligence-based applications, accompanied by demonstrations and hands-on practice sessions. Based on the results of discussions and evaluations conducted, training participants experienced an increase in knowledge and utilization of artificial intelligence-based teaching media, resulting in improved learning quality, increased teacher creativity in developing artificial intelligence-based teaching media, and improved teacher ability to apply artificial intelligence-based teaching media, thereby creating innovative digital classrooms.